Drug Profile and Therapeutic Adherence of African-Brazilians with Apparent Resistant Hypertension - Barletta,Pedro Henrique Andrade Araújo Salvatore (2021)
Abstract Background Resistant hypertension (RH) is manifested by the presence of blood pressure values resistant to antihypertensive therapy. RH is highly prevalent among black individuals, increasing cardiovascular risk in this population and requiring effective control of this comorbidity. Objectives To investigate the medication profile and therapeutic adherence in black people with apparent RH. Methods This is a cross-sectional study, with a convenience sample of individuals with apparent RH. Data were obtained from medical records. Therapeutic adherence was assessed using the Morisky Therapeutic Adherence Scale of 8 items (MMAS-8) and statistical analysis was performed using the SPSS, version 23. Significance was set at p <0.05. Results Of the 120 individuals, 90 (75%) were women and 72 (60%) were black. Mean SBP was 153.09 (SD 25.59) mm Hg and mean DBP, 90.82 (SD 16.91) mm Hg, with a statistical difference in relation to the target pressure for SBP. Regarding the medication profile, 79.2% of the individuals used the recommended regimen for RH (ACEI / ARB + Diuretic + CCB), with the fourth most used drug being beta-blockers. The average score in MMAS-8 was 6.62 (SD 1.38) points, with 19.2%, 50.0%, and 30.8% showing low, medium, and high adherence, respectively. Conclusions It was evidenced that two-thirds of the individuals did not have high therapeutic adherence and not all used the ideal regimen for the management of RH, nor full doses. Thus, most individuals were probably affected by pseudoresistance, which was initially diagnosed as apparent RH. (Int J Cardiovasc Sci. 2021; [online].ahead print, PP.0-0)